2006
DOI: 10.1002/jclp.20325
|View full text |Cite
|
Sign up to set email alerts
|

Examining the links between spiritual struggles and symptoms of psychopathology in a national sample

Abstract: The present study investigated the relationship between spiritual struggles and various types of psychopathology symptoms in individuals who had and had not suffered from a recent illness. Participants completed self-report measures of religious variables and symptoms of psychopathology. Spiritual struggles were assessed by a measure of negative religious coping. As predicted, negative religious coping was significantly linked to various forms of psychopathology, including anxiety, phobic anxiety, depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
203
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(226 citation statements)
references
References 39 publications
12
203
0
8
Order By: Relevance
“…Several studies support the incremental validity of the NRC scale [28,31,32,44,[49][50][51]. In one such study, NRC remained a significant predictor of IL-6 levels among cardiac patients after controlling for a number of other biomedical indicators and mood states.…”
Section: Incremental Validitymentioning
confidence: 90%
See 2 more Smart Citations
“…Several studies support the incremental validity of the NRC scale [28,31,32,44,[49][50][51]. In one such study, NRC remained a significant predictor of IL-6 levels among cardiac patients after controlling for a number of other biomedical indicators and mood states.…”
Section: Incremental Validitymentioning
confidence: 90%
“…In another study, NRC significantly predicted lower quality of life among advanced cancer patients after controlling for self-efficacy, history of depression and demographic variables [51]. Other studies have demonstrated that NRC can predict outcomes even after controlling for an index of general religiousness-in addition to other relevant demographic, biomedical, and psychological variables [31,49,50]. Sherman, Simonton, Latif, Spohn and Tricot [31] found that, among multiple myeloma patients undergoing stem cell transplantation, NRC remained positively associated with total distress and depression after controlling for demographic and medical variables as well as general religiousness.…”
Section: Incremental Validitymentioning
confidence: 93%
See 1 more Smart Citation
“…R/S struggles are not at all unusual among college students (Bryant and Astin 2008;Johnson and Hayes 2003) or the general U.S. population (Abu-Raiya et al 2015;Ellison and Lee 2010;McConnell et al 2006). Furthermore, a myriad of cross-sectional research suggests that experiences of R/S struggles relate to negative life outcomes (e.g., Abu-Raiya et al 2015;Wilt et al 2017; for reviews, see Exline 2013;Exline and Rose 2005;Wilt et al 2018a).…”
Section: Religious and Spiritual Strugglesmentioning
confidence: 99%
“…Spirituality was also found to protect against loneliness in a review study of Victor, Scambler, Bond, and Bowling (2000). McConnell, Pargament, Ellison, and Flannelly (2006) studied 1629 participants with an average age of 49 years and reported that those with low levels of spiritual practices might have increased tendencies to develop anxiety and depression. A recent study showed that higher spiritual levels reduced anxiety among 143 older people after controlling for personality, gender and education levels (MacKinlay & Burns, 2017).…”
Section: The Use Of a Spiritual Approach To Adaptationmentioning
confidence: 99%